1990
DOI: 10.24199/j.mmv.1990.50.02
|View full text |Cite
|
Sign up to set email alerts
|

Prionospio and Paraprionospio (Polychaeta: Siphonidae) from southern Australia

Abstract: Wilson, R.S., 1990. Prionospio and Paraprionospia (Polychaeta: Spionidae) from sou-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 9 publications
4
53
1
1
Order By: Relevance
“…Remarks: The Mediterranean specimens of Paraprionospio coora closely agree with the original description of the species from Australia by WILSON (1990), but have 2-3 pairs of apical teeth in neuropodial hooded hooks rather than only 2 pairs of apical teeth. A variable number of apical teeth was noted within the Mediterranean specimens, suggesting that this is not a stable characteristic to be used in distinguishing species.…”
Section: Taxonomic Accountsupporting
confidence: 65%
See 4 more Smart Citations
“…Remarks: The Mediterranean specimens of Paraprionospio coora closely agree with the original description of the species from Australia by WILSON (1990), but have 2-3 pairs of apical teeth in neuropodial hooded hooks rather than only 2 pairs of apical teeth. A variable number of apical teeth was noted within the Mediterranean specimens, suggesting that this is not a stable characteristic to be used in distinguishing species.…”
Section: Taxonomic Accountsupporting
confidence: 65%
“…2d) instead of the slender filament in some of the other Paraprionospio species (see Figs 1,10,11,13,14 in YOKOYAMA, 2007). WILSON (1990), YOKOYAMA (2007) andZHOU et al (2008) did not mention this characteristic however, we found the same structure in the Japanese specimens of P. coora. Hence, we identified the Mediterranean specimens as P. coora.…”
Section: Taxonomic Accountmentioning
confidence: 55%
See 3 more Smart Citations